HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT DEPRESI PADA LANSIA DI POSYANDU SEJAHTERA GBI SETIA BAKTI KEDIRI - Astuti, VItaria Wahyu (Jurnal Penelitian STIKES Kediri, 2010)
Background    : Depression is mood interference that usually happened to elderly, there can caused elderly feel separated / isolated from family and feel loneliness. To overcome depression is different, according to patient condition. But support from family more help elderly to prevent and overcome elderly depression. From family support, elderly may feel to be attended so elderly can enter old day better. This research have objective to analize relationship family support and depression level of elderly in Posyandu Sejahtera GBI Setia Bakti Kediri.   Method            : research used analytic design that was correlation study. The populates of this research were all elderly, who life whithis child and grand child. Amount of sample were 61 respondents, taken by purposive sampling. This research used Spearman Rho’s statistic test whit SPSS 11 version, and have significant meaning r ≤ 0,05. Result of this research showed family support that elderly felt was good support, there were 56 respondents (91,8%).   Conclusion      : This conclusion of this research showed there was relationship between family support and family depression of elderly in Posyandu Sejahtera GBI Setia Bakti Kediri. It mean that a good family support make elderly feeling comfortable, and elderly had a good coping to solve their problems so that elderly had low / mild depression level.